Knowledge roadmap of sustainable development in the textile and apparel industry: a scientometric analysis - Zhaoshan Wu; Liya Zhou; Xuemei Ding; Xiongying Wu; Laili Wang (Fashion and Textiles, 2022)
Abstract Practices in the textile and apparel industry (TAI) have led to numerous environmental and social problems, which have prompted extensive research on the sustainable development of the textile and apparel industry (SDTAI). This paper presents a comprehensive and quantitative analysis of the status quo in the SDTAI domain using scientometrics. From 1987 to 2019, the Web of Science core collection databases (SCI and SSCI) included 863 journal articles related to SDTAI, and our analysis results were as follows: (1) 60 critical research keywords occur in the knowledge base; (2) four research hotspots were identified; (3) five themes constituted the main knowledge area; and (4) based on the knowledge base, research hotspot, and knowledge domain, the knowledge structure consisted of nine subjects and five systems. This paper proposes a knowledge roadmap that can be helpful for practitioners and academicians to better understand the current sustainable development status and trends in the TAI.